Natural deep eutectic solvent-based microwave-assisted extraction in the medicinal herb sample preparation and elemental determination by ICP OES - Costa, Floriatan Santos; Moreira, Luana Santos; Silva, Alisson Moreira; Silva, Rafael J.; dos Santos, Mayara Padovan; da Silva, Erik Galvão Paranhos; Grassi, Marco Tadeu; Gonzalez, Mario Henrique [UNESP]; Amaral, Clarice D.B. (Elsevier, 2022)
In this study, a microwave-assisted extraction (MAE) method based on the natural deep eutectic solvent (NADES) was developed for the Cd, Cu, Fe, Mn, and Zn determination in medicinal herb samples. The experimental conditions were optimized and the method parameters were evaluated using certified reference material. The NADES composed of choline chloride-oxalic acid prepared in a microwave system showed better extraction rates and low-energy consumption. Optimal conditions in the MAE were obtained using 35 s of extraction time, 90% of microwave power, and a 50 mg/mL sample-solvent ratio. Recoveries in the range of 87–109% and relative standard deviation < 8.45% were obtained. The limits of quantification (mg kg-1) were: 0.0233 (Cd), 0.0229 (Cu), 1.10 (Fe), 0.06 (Mn), and 0.67 (Zn). The medicinal herbs were analyzed and daily intake values were estimated for Cu (<0.20%), Fe (<18.1%), Mn (<13.8%), and Zn (<0.64%); concentrations above threshold values for Cd were found. The optimization of experimental conditions combined and the use of an eco-friendly solvent provided excellent analytical parameters in the proposed method.
Keywords: Eco-friendly solvent; Elemental determination; Experimental design; Food analysis; Green analytical chemistry; Medicinal herbs